Chemostratigraphy of the Toarcian oceanic anoxic event from the Ionian Zone, Greece - Kafousia, N.; Karakitsios, V.; Mattioli, E.; Jenkyns, H.C. (Bulletin of the Geological Society of Greece, 2013)
A global perturbation in the carbon cycle has been recorded in the Early Toarcian ( 183 Ma) and is marked by enhanced organic-carbon burial and mass extinction. It is also associated with high palaeotemperatures, both positive and negative excursions in carbon-isotope ratios, and the development of anoxic to euxinic conditions in marine environments: together these phenomena have been designated as constituting an Oceanic Anoxic Event. Here we provide a high-resolution, multiproxy biostratigraphic and chemostratigraphic study from a section that belongs to the central Ionian Zone in Greece. Calcareous nannofossil distribution, as well as the TOC, δ13Ccarb and δ13Corg, have all been determined. The nannofossil zones NJT 5b, NJT 6 and NJT 7 have been recognized in the section. In the NJT 5b zone a small positive excursion in TOC and negative excursion in δ13Ccarb is recorded, tentatively assigned to the Pliensbachian/Toarcian boundary. In the NJT 6 zone, the main negative carbon-isotope excursion characteristic of this interval is developed, associated with a relative increase in TOC. The difference in this section, compared with sections from the Pindos Zone but in common with sections elsewhere, is the record of a positive excursion in the NJT 7 zone in both organic and carbonate carbon isotopes. This study offers new biostratigraphic and geochemical data for the Ionian Zone, and further illustrates the impact of Toarcian Oceanic Anoxic Event in the Tethyan region.